Severe Hypokalemic Myopathy With Very High Creatine Kinase as the First Manifestation of Primary Hyperaldosteronism - An Unusual Presentation of a Rare Disorder - Tasnim, Refaya; Jahan Mithi, Mir Tangila; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2022)
Hypokalemia is one of the most common electrolyte imbalances to be encountered in clinical practice. The kidney is the primary actor that maintains long term potassium homeostasis and regulates serum level around a narrow range of 3.5-5.5mmol/L. There is a long list of common causes for hypokalemia; apart from these, rare diseases should not slip our mind while treating such a case. Regarding clinical features, muscular weakness accounts for a common one; however occasionally, severe hypokalemia can cause myopathy and/or rhabdomyolysis. Here, we present the case of a middle-aged man, who brought up to us with severe muscular weakness owing tohypokalemia; which was later found to be the rare clinical entity of a rare disorder - primary hyperaldosteronism (PH). In this article, we as well focused on the pathophysiological basis ofPH and hypokalemia leading to myopathy. Bangladesh J Medicine 2022; 33: 224-228